2011
DOI: 10.1021/ol201475j
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkably Simple Protocol for the N-Formylation of Amino Acid Esters and Primary Amines

Abstract: A simple, convenient, and wide scope protocol for the N-formylation of amino acid esters and primary amines has been developed utilizing only imidazole in warm DMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 33 publications
1
53
0
3
Order By: Relevance
“…[5] Very recently, Hudson et al developed a simple, convenient protocol for the N formylation of amino acid esters and primary amines utilizing only imidazole in warm DMF. [9] A wide scope of amino acid esters were formylated by this transformation. Importantly, no racemization was observed during the reactions, and the authors have proposed a plausible mechanism for this reaction as depicted in Scheme 3.…”
Section: Serving As a Precursor In Formylation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Very recently, Hudson et al developed a simple, convenient protocol for the N formylation of amino acid esters and primary amines utilizing only imidazole in warm DMF. [9] A wide scope of amino acid esters were formylated by this transformation. Importantly, no racemization was observed during the reactions, and the authors have proposed a plausible mechanism for this reaction as depicted in Scheme 3.…”
Section: Serving As a Precursor In Formylation Reactionsmentioning
confidence: 99%
“…In this context it was found that the combination of DMF and NH 4 HCO 3 delivered the cyano product in low yield [Eq. (9) in Scheme 25]. [42] Subsequently, they reported the coppermediated cyanation of aryl halides with the combined cynanide source of DMF and NH 4 HCO 3 (Scheme 25).…”
Section: Serving As a Precursor In Cyanation Reactionsmentioning
confidence: 99%
“…DMF eine ausgereifte Methodik, wie Muzart in seiner Übersicht beschreibt. [5] Eine sehr einfache Methode zur N-Formylierung von Aminosäuren und primären Aminen nur mit Imidazol in warmem DMF entwickelten kürzlich Hudson et al [9] Auf diese Weise formylierten sie ein breites Spektrum von Aminosäuren, ohne dass diese racemisierten. Der von den Autoren vorgeschlagene Mechanismus ist in Schema 3 dargestellt.…”
Section: Dmf Als Vorstufe In Formylierungenunclassified
“…Die Kombination von DMF und NH 4 HCO 3 brachte bei dieser Reaktion nur geringe Ausbeute an cyaniertem Produkt [Gl. (9) in Schema 25]. [42] Danach beschrieben die Autoren eine kupferkatalysierte Cyanierung von Arylhalogeniden mit der Kombination von DMF und NH 4 HCO 3 als Quelle für CN (Schema 25).…”
Section: Dmf Als Vorstufe In Cyanierungenunclassified
“…The reaction was monitored by IR and GC-MS analysis. All the products were characterized by NMR, IR, and MS (EI+) and compared with literature(Bao et al 2008;Brahmachari and Lasakr 2010;Das et al 2008;Ma'mani et al 2010;Saladino et al 2006;Shekhar et al 2009;Suchý et al 2011).…”
mentioning
confidence: 99%